Structural prediction of protein models using distance restraints derived from cross-linking mass spectrometry data - Orbán-Németh, Zsuzsanna; Beveridge, Rebecca; Hollenstein, David M; Rampler, Evelyn; Stranzl, Thomas; Hudecz, Otto; Doblmann, Johannes; Schlögelhofer, Peter; Mechtler, Karl (Nature protocols, 2018)
This protocol describes a workflow for creating structural models of proteins or protein complexes using distance restraints derived from cross-linking mass spectrometry experiments. The distance restraints are used (i) to adjust preliminary models that are calculated on the basis of a homologous template and primary sequence, and (ii) to select the model that is in best agreement with the experimental data. In the case of protein complexes, the cross-linking data are further used to dock the subunits to one another to generate models of the interacting proteins. Predicting models in such a manner has the potential to indicate multiple conformations and dynamic changes that occur in solution. This modeling protocol is compatible with many cross-linking workflows and uses open-source programs or programs that are free for academic users and do not require expertise in computational modeling. This protocol is an excellent additional application with which to use cross-linking results for building structural models of proteins. The established protocol is expected to take 6-12 d to complete, depending on the size of the proteins and the complexity of the cross-linking data.